Acupuncture and osteopathic medicine for atopic dermatitis: a three‐armed, randomized controlled explorative clinical trial. (1st December 2022) - Rotter, Gabriele; Ahnert, Moritz W.; Geue, Anne V.; Icke, Katja; Binting, Sylvia; Tissen‐Diabaté, Tatjana; Roll, Stephanie; Ortiz, Miriam; Reinhold, Thomas; Kass, Benjamin; Staab, Doris; Pfab, Florian; et al.
Abstract: Background: Patients with atopic dermatitis (AD) frequently use acupuncture (ACU) and osteopathic medicine (OM), although their therapeutic benefits are unclear. Aim: To investigate the effectiveness of ACU and OM in patients with AD. Methods: In a three‐armed, single‐centre, randomized controlled open explorative clinical trial, adult patients with AD received ACU, OM or no study intervention (control group; CG) plus routine care. Outcomes included disease severity (SCORing Atopic Dermatitis; SCORAD), itching intensity (visual analogue scale; VAS), frequency of topical corticosteroid (TCS) use over 7 days and cost‐effectiveness. Endpoints were analysed by analysis of covariance adjusted for the respective baseline value and TCS use. Results: Overall, 121 patients (92 women, 29 men) with a mean ± SD age of 31.4 ± 10.5 years were randomized. After 12 weeks, the adjusted means (95% CI) for ACU, OM and control were, respectively, 22.3 (18.3–26.3), 26.4 (22.6–30.2) and 23.7 (19.9–27.5) for SCORAD (P = 0.32); 27.9 (19.5–36.4), 35.0 (26.9–43.0) and 42.3 (34.7–50.0) for VAS itching (P < 0.05); and 2.3 (0.8–3.9), 1.9 (0.4–3.5) and 4.3 (2.6–6.0), for TCS use (P = 0.10). ACU and OM were not cost‐effective compared with the CG. Conclusion: Although no differences in disease severity were found, our findings indicate that ACU might reduce itching in patients with AD. Furthermore, ACU and OM showed a trend towards reducing TCS use. Abstract : We present the results of a trial of acupuncture and osteopathic medicine for treating atopic dermatitis (AD). Although no differences in disease severity were found, our findings indicate that acupuncture might reduce itching in patients with AD. Furthermore, acupuncture and osteopathic medicine show a trend towards reducing topical corticosteroid use in patients with AD.